2010
DOI: 10.1152/ajpgi.00046.2010
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of proliferation in the colorectal mucosa by gastrin precursors is blocked by desferrioxamine

Abstract: Precursors of the peptide hormone gastrin stimulate proliferation in the colorectal mucosa and promote the development of colorectal carcinoma. Gastrins bind two ferric ions selectively and with high affinity, and the biological activity of glycine-extended gastrin (Ggly) in vitro is dependent on the presence of ferric ions. The aim of the present study was to determine whether or not iron is required for biological activity of progastrin and Ggly in vivo. Rats that had undergone a colostomy were infused with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
4
11
1
Order By: Relevance
“…Contrary to our data, in many cancer cells an increase in LIP leads to augmented cell proliferation [33,34]. Possibly, it is associated with high JNK activity in many rapidly proliferating cancer cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our data, in many cancer cells an increase in LIP leads to augmented cell proliferation [33,34]. Possibly, it is associated with high JNK activity in many rapidly proliferating cancer cells.…”
Section: Discussioncontrasting
confidence: 99%
“…17 Indeed, the identity of a progastrin receptor remains an issue of intense investigation. Recent studies have suggested that Annexin A2, 32,33 ferric ions, 34 and charged glycosaminoglycans 17 are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have shown that the F 1 -ATPase, which directly binds G-gly, is present at the plasma membrane of colonic epithelial cells in a mouse model. It is also interesting to notice that in both in vivo models (G-gly transgenic mice or G-gly infusion), treatment of the animals with DFO, a ferric ions chelating agent, reverses the proliferative effects induced by G-gly, suggesting that the biological activity of the peptide is dependent on the presence of ferric ions (34). In vitro studies confirm that G-gly binds two ferric ions necessary to its biological activity (9,25,26).…”
Section: Discussionmentioning
confidence: 94%